Comparison of Gas Sensing Properties of Reduced Graphene Oxide Obtained by Two Different Methods - Sabina Drewniak; Marcin Procek; Roksana Muzyka; Tadeusz Pustelny (Sensors, 2020)
In this study, the sensitivity of reduced graphene oxide structures (rGO) to the action of selected gases (especially hydrogen, but also nitrogen dioxide and ammonia) was examined. Two sensing structures, based on rGO structures, obtained by different methods of oxidation (the modified Hummers, and the modified Tour’s method respectively), were investigated. We show here that the method used for the oxidation of rGO influences the sensitivity of the sensing structure during contact with various gaseous atmospheres. We performed our experiments in the atmosphere, containing hydrogen in a concentration range from 0 to 4% in nitrogen or synthetic air, both in dry and wet conditions. The temperature range was from 50 °C to 190 °C. Finally, we checked how the resistance of the samples changes when the other gases (NO2, NH3) appear in tested gas mixtures. The gas investigations were supplemented by the characterization of rGOs materials using scanning electron microscopy (SEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and N2 sorption method.